2010
DOI: 10.1086/648591
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cell‐Mediated Immunogenicity of DNA/DNA, DNA/Adenovirus Type 5 (Ad5), or Ad5/Ad5 HIV‐1 Clade BgagVaccine Prime‐Boost Regimens

Abstract: The DNA vaccine alone or as a priming regimen for the Ad5 vaccine did not increase unfractionated ELISpot responses compared with the Ad5 vaccine alone. Qualitative T cell responses to different vaccine regimens deserve further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 38 publications
(54 reference statements)
1
49
1
Order By: Relevance
“…rAd5 genetic vaccines for EBOV provide potent protective immunity in macaques and have been proven safe and immunogenic in human clinical trials (2,12,16,21). Studies of macaques and humans have shown that preexisting vector-directed immunity can limit the potency of viral vector-based vaccines (5,29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…rAd5 genetic vaccines for EBOV provide potent protective immunity in macaques and have been proven safe and immunogenic in human clinical trials (2,12,16,21). Studies of macaques and humans have shown that preexisting vector-directed immunity can limit the potency of viral vector-based vaccines (5,29).…”
Section: Resultsmentioning
confidence: 99%
“…Adenovirus-based vaccines have several advantages as human vaccines-they can be produced to high titers under good manufacturing practice (GMP) conditions and have proven to be safe and immunogenic in humans (2,6,12,16,18). While most of the initial vaccine work was conducted using rAd serotype 5 (rAd5) due to its significant potency in eliciting broad antibody and CD8 ϩ T-cell responses, preexisting immunity to rAd5 in humans may limit efficacy (5)(6)(7)29).…”
mentioning
confidence: 99%
“…In addition there was a trend toward greater magnitude of ICS and greater breadth across proteins in group A than B. This hidden priming effect, where the immune response quality is enhanced by the DNA prime, has been seen in trials where adenoviral or poxvirus vectors are used as a boost (18,23,24,26,45,48). The immune response quality and quantity appear to be enhanced by the "hidden" DNA prime and manifests itself by increased polyfunctionality of the T cells and increased numbers of terminally differentiated T cells with a cytotoxic effector potential (19,52).…”
Section: Figmentioning
confidence: 91%
“…The DNA backbone, dose, number of administrations, insert, and method of delivery are all variables associated with effectiveness of the DNA (8,46,47). Some studies have shown that DNA alone is immunogenic in humans, albeit with low-magnitude responses as measured by ELISPOT and/or ICS (26,48,49). Use of Biojector does not seem to enhance immune responses to DNA in either humans or nonhuman primates, though few studies have directly compared standard intramuscular administration of DNA to Biojector in humans (49)(50)(51).…”
Section: Figmentioning
confidence: 99%
“…This candidate was advanced to a Phase IIb efficacy evaluation that was stopped at a scheduled interim analysis when it was apparent that there was no effect on postinfection viral RNA level (Buchbinder et al 2008), despite demonstration of apparent immunogenicity in Phase I clinical trials and evidence of viral load control in the SHIV/NHP model (Shiver et al 2002;Casimiro et al 2003;Wilson et al 2006;Priddy et al 2008;Harro et al 2009;Asmuth et al 2010). Although mechanisms underlying failure of this vaccine remain elusive, one explanation is that this homologous vector vaccine, which elicits frequent IFN-g ELISpot responses (77% of vaccinees overall) when given in three doses, generates a limited breadth of antigen-specific responses (McElrath et al 2008).…”
Section: Adenoviral Vector Vaccine Trialsmentioning
confidence: 99%